Marketing analysis of diversification of the factors determining the market conditions of the space tourism market - Vovchanska, Olha; Ivanova, Liliya (Turystyka i Rozwój Regionalny, 2022)
The study is dedicated to the marketing analysis of the diversification of the factors affecting the formation and development of the market conditions of the space tourism market. The article summarizes scientific approaches to the definition of space tourism, systematizes the features of the formation and development of the global space tourism market, and analyses the indicators of the development of the space tourism market in the leading spacefaring countries of the world. The actual determinants of the development of the world market of space tourism have been identified, as well as main motivational factors of space tourists. The main endogenous and exogenous factors for the development of the space tourism market were investigated. Attention was focused on the fact that the modern economic mechanism for the development of the space tourism market is based on the concept of marketing with its main elements adapted. Marketing directions for the popularization of tourist space flights were researched. It is concluded that the space tourism market has a huge potential. Space travel has become a reality, and in the foreseeable future space tourism will become massive, while the industry of space experiences will develop at an accelerated pace, stimulating the emergence of other lucrative sub-markets.